A Bibliometric Analysis of Vocational School Keywords Using VOSviewer - Dwi Novia Al Husaeni; Asep Bayu Dani Nandiyanto (ASEAN Journal of Science and Engineering Education, 2023)
A vocational school is a secondary education institution that prepares students to work in their fields of study. The goal of this study was to combine mapping analysis with VOSviewer software to conduct bibliometric engineering research at a vocational school. VOSviewer and Publish or Perish were the applications used in this study. "Vocational School" is the research's keyword. Based on the findings of a search of 990 relevant articles published between 2017 and 2021. According to the findings, research on vocational schools decreased from 2017 to 2020 before increasing in 2021. The importance of bibliometric analysis in providing data analysis about what phenomena occur is demonstrated in this study. It is hoped that this research will assist and serve as a reference for researchers in conducting and determining the research theme to be pursued.